PERANG PEREBUTAN IRIAN BARAT: SEBUAH TINJAUAN HISTORIS - Andhika Putra, Doly; Ghazalie, Ghazalie (Jurnal Praksis dan Dedikasi Sosial, 2024)
THE WAR FOR WESTERN IRIAN: A HISTORICAL OVERVIEW This paper aims to provide a comprehensive understanding of the political, military, and diplomatic dynamics surrounding the struggle of West Irian, with a specific focus on its integration into the Unitary State of the Republic of Indonesia (NKRI). The research details the agreements between Indonesia and the Netherlands concerning West Irian, observing not only the international diplomatic aspects of that era but also initiating discussions on the contemporary relevance of this issue. This study employs a critical historical method in the process of data collection. The heuristic stages involve discovering and collecting various information sources related to the research theme. The study's findings indicate that the combination of local resistance, diplomacy, and the spirit of Indonesian nationalism effectively ended Dutch domination and integrated West Irian into the archipelago. This highlights the importance of sovereignty and territorial integrity for a nation. Penelitian ini bertujuan untuk memberikan pemahaman yang komprehensif mengenai dinamika politik, militer, dan diplomatik yang melingkupi perebutan Irian Barat, dengan fokus khusus pada integrasi Irian Barat ke dalam Negara Kesatuan Republik Indonesia (NKRI). Penelitian ini merinci perjanjian-perjanjian antara Indonesia dan Belanda mengenai Irian Barat, dengan mengamati tidak hanya aspek-aspek diplomatik internasional pada masa itu, tetapi juga menginisiasi diskusi mengenai relevansi kontemporer dari masalah ini. Penelitian ini menggunakan metode sejarah kritis dalam proses pengumpulan data. Tahapan heuristik melibatkan penemuan dan pengumpulan berbagai sumber informasi yang berkaitan dengan tema penelitian. Temuan penelitian ini menunjukkan bahwa kombinasi antara perlawanan lokal, diplomasi, dan semangat nasionalisme Indonesia secara efektif mengakhiri dominasi Belanda dan mengintegrasikan Irian Barat ke dalam wilayah nusantara. Hal ini menyoroti pentingnya kedaulatan dan integritas teritorial bagi sebuah negara.